Plasticizers May Activate Human Hepatic Peroxisome Proliferator-Activated Receptor α Less Than That of a Mouse but May Activate Constitutive Androstane Receptor in Liver - Yuki Ito; Toshiki Nakamura; Yukie Yanagiba; Doni Hikmat Ramdhan; Nozomi Yamagishi; Hisao Naito; Michihiro Kamijima; Frank J. Gonzalez; Tamie Nakajima (PPAR Research)
Dibutylphthalate (DBP), di(2-ethylhexyl)phthalate (DEHP), and di(2-ethylhexyl)adipate (DEHA) are used as plasticizers. Their metabolites activate peroxisome proliferator-activated receptor (PPAR) α, which may be related to their toxicities. However, species differences in the receptor functions between rodents and human make it difficult to precisely extrapolate their toxicity from animal studies to human. In this paper, we compared the species differences in the activation of mouse and human hepatic PPARα by these plasticizers using wild-type (mPPARα) and humanized PPARα (hPPARα) mice. At 12 weeks old, each genotyped male mouse was classified into three groups, and fed daily for 2 weeks per os with corn oil (vehicle control), 2.5 or 5.0 mmol/kg DBP (696, 1392 mg/kg), DEHP (977, 1953 mg/kg), and DEHA (926, 1853 mg/kg), respectively. Generally, hepatic PPARα of mPPARα mice was more strongly activated than that of hPPARα mice when several target genes involving β-oxidation of fatty acids were evaluated. Interestingly, all plasticizers also activated hepatic constitutive androstane receptor (CAR) more in hPPARα mice than in mPPARα mice. Taken together, these plasticizers activated mouse and human hepatic PPARα as well as CAR. The activation of PPARα was stronger in mPPARα mice than in hPPARα mice, while the opposite was true of CAR.